Intensive writing (First Edition, 2018)
?intensive writing? is one of the compulsory subjects taught to the first semester students of english language education study program of khairun university. as an effort to improve the quality of graduates of the study program, continuous improvement in teaching and learning process including the subject knowledge and teaching and learning process has been made in accordance with changing needs and era. this book has been written to fulfil the need of improving students? knowledge and skills on some aspects of writing skills in english. this book has been written within the Indonesian higher education curriculum in line with the national standard of higher education and the Indonesian national qualification framework. as recommended by the director general of learning affairs of the ministry of research, technology, and higher education of the republic of indonesia, the topics presented in this book apply student centred learning principles such as discussion and group work. such learning principles allow the students to learn the topics through critical thinking, analytical, inductive, deductive, and reflective processes that lead to higher order thinking through creative and participatory discussions. in this book, concepts relating to each topic (such as paragraph, capitalization and punctuation, descriptive paragraph and so on) discussed are presented followed by its example(s) and practice(s) as a guideline. in the writing class, however, it is suggested that classroom activities should start with an inductive process meaning that examples of each topic are presented to students first and the teacher facilitates the students to identify and allow them familiar with the concepts drawn from the examples. then, through a deductive process the students do practice(s) in each topic to apply the intended concepts into their language performance such as writing a paragraph, using correct capitalization and punctuation in text, writing a descriptive paragraph.